2020
DOI: 10.1186/s12884-020-03328-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal demographic and antenatal factors, low birth weight and preterm birth: findings from the mother and child in the environment (MACE) birth cohort, Durban, South Africa

Abstract: Background Low birthweight (LBW) and preterm birth (PB) remain the leading cause of morbidity and mortality in neonates worldwide. The aim of this study was to identify maternal demographic and antenatal factors associated with PB and LBW among low socio-economic communities. Methods Pregnant women (n = 1099) were recruited in the first trimester into the Mother and Child in the Environment (MACE) birth cohort in Durban, South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The prevalence of LBW in the sample was 14.7% and is closely aligned with recent cohort studies of birthweight in South Africa (Budree et al, 2017 ; Jeena et al, 2020 ). We found that child hunger in the household was significantly associated with low birthweight but adult hunger was not.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The prevalence of LBW in the sample was 14.7% and is closely aligned with recent cohort studies of birthweight in South Africa (Budree et al, 2017 ; Jeena et al, 2020 ). We found that child hunger in the household was significantly associated with low birthweight but adult hunger was not.…”
Section: Discussionsupporting
confidence: 88%
“…In the South African context, studies of two longitudinal cohorts have observed associations with LBW in mothers who smoke or drink alcohol as well as those with overweight or obese BMI (Budree et al, 2017 ; Jeena et al, 2020 ). An unpublished thesis study among pregnant women in an urban area of South Africa found no association with household food insecurity and low birthweight while another birth cohort study in South Africa found that food insecurity was associated with lower infant gestational age (Zar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, preeclampsia is a risk factor for the development of perinatal outcomes [ 36 , 37 ] and the use of paracetamol during pregnancy increases the risk of preeclampsia [ 34 ]. In addition, the analyzes were not adjusted for other factors that increase the risk of perinatal outcomes, such as smoking [ 38 , 39 ] and the use of drugs of abuse [ 40 , 41 ] during pregnancy, because the number of pregnant women with these habits in the study was very small. In addition, some covariates such as chronic diseases, acute diseases, history of PTB, and history of LBW were not included because a large number of data were missing.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one pregnant woman reported antidepressant use (citalopram) at enrolment, in line with the very limited access to psychiatric services in underserved communities in the South African population ( Seedat et al, 2008 ). The present study used a lenient definition of the exclusion criterion preterm birth (1 week below the standard definition of 37 weeks gestation; World Health Organization (1997) ) to account for the relatively high frequency of preterm births in South Africa ( Chawanpaiboon et al, 2019 , Jeena et al, 2020 ). While early brain development following AMD exposure in children born late preterm is epidemiologically relevant, especially in LMIC settings, sensitivity analyses were conducted to ensure the findings also applied to term infants.…”
Section: Discussionmentioning
confidence: 99%